FRACTURE ANALYSIS AND IMPROVEMENT RESEARCH OF CUTTING SPINDLE FOR A BOOM ROADHEADER - SONG Yu; LI YunPeng; ZHANG HongTao; CHEN Liang; DANG QiQian (Jixie qiangdu)
In order to find out the cause of the fracture of the cutting spindle as one of the key components of a cantilever roadheader, and to solve this fracture problem, this paper analyzes it in multiple ways and proposes an improved scheme. Through the analysis of fracture surface macro-morphology, material chemical composition, mechanical properties, microstructure and finite element stress of the cutting spindle, the failure conclusion is drawn and the corresponding improvement scheme is put forward. The results show that the cutting spindle in the actual complex working conditions, due to machining and heat treatment in the process of shortcomings, as well as the use of abnormal operation, resulting in the operation of the stress concentration in the greater position of fracture failure. According to the failure reasons, the corresponding improvement schemes are put forward: by optimizing the structure and improving the processing, reducing the stress concentration, improving the heat treatment process, improving its mechanical properties and other methods to improve the performance of the shaft to meet its functional requirements. The results of this study can provide a good reference value in solving the problem of failure of shaft transmission parts and improving the performance of shaft transmission parts.